Odpowiedź :
Odpowiedź:
(-6)² = -6×(-6) = 36
(-3)³ = -3×(-3)×(-3) = -27
(1/6)² = 1/6×1/6 = 1/36
(1/3)³ = 1/3×1/3×1/3 = 1/27
(-1/6)² = -1/6×(-1/6) = 1/36
(-1/3)³ = -1/3×(-1/3)×(-1/3) = -1/27
Szczegółowe wyjaśnienie:
Odpowiedź:
______________________________
-6^2 = -6 * -6 = -36
______________________________
-3^3 = -3 * -3 * -3 = -27
______________________________
1/6^2 = 1/6 * 1/6 = 1/36
______________________________
1/3^3 = 1/3 * 1/3 * 1/3 = 1/27
______________________________
(-1/6)^2 = (-1/6) * (-1/6) = 1/36
______________________________
(-1/3)^3 = (-1/3) * (-1/3) * (-1/3) = -1/27
______________________________
^ - do potęgi
/ - kreska ułamkowa
Szczegółowe wyjaśnienie:
Mam nadzieję że pomogłam :)